1980
DOI: 10.1002/1097-0142(19800301)45:5<954::aid-cncr2820450520>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Congenital generalized fibromatosis with visceral involvement. A case report

Abstract: A case of congenital generalized fibromatosis in a black male infant with involvement of lungs, subcutaneous tissue, pancreas, adrenal, lymph nodes, and bone is described. Fifteen prior cases with pulmonary involvement are reviewed, emphasizing the poor prognosis associated with pulmonary lesions. This case demonstrated, in addition to previously described histologic features, broad bands of fibroblastic proliferation in the interlobular septa producing retraction of the visceral pleura. Possible etiologic fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…Symptoms depend on the location and occur with local invasion to adjacent tissues (7). The patients with intraabdominal DT generally have no symptoms and are encountered incidentally during laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms depend on the location and occur with local invasion to adjacent tissues (7). The patients with intraabdominal DT generally have no symptoms and are encountered incidentally during laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Our case is the twenty-first case of a pancreatic DT reported in the English literature; twenty previous cases have been identified and are summarized in Table 1 [7,9,11,16,[34][35][36][37][38][39][40][41][42][43][44][45]. DTs occurring in the pancreas, unlike other intra-abdominal DTs, are most commonly sporadic with only one reported pancreatic tail solid/cystic DT reported to be associated with FAP.40 Tumors were equally distributed between genders (12 males and 9 females).…”
Section: Discussionmentioning
confidence: 99%
“…However, vascular damage of large blood vessels is less frequent. Lesions of the pulmonary vein and other large veins have been described occasionally [7,8]. Wright et al have reported a patient with multifocal IM who subsequently developed several aneurismal dilations of the arterial system including the thoracic and abdominal aorta, carotid, iliac, and lower limb vessels.…”
Section: Discussionmentioning
confidence: 99%